In a Pinch: Snow Crab and the Politics of Crisis in Newfoundland - Davis, Reade; Korneski, Kurt (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2012)
Drawing on historical sources and interviews, this paper discusses several key forces that have shaped the development of the snow crab (Chionoecetes opilio) fishery in Newfoundland. Once commonly discarded as a pest, snow crab has emerged as the economic foundation of many rural coastal communities since the cod moratorium of the early 1990s. While this fishery has brought unprecedented prosperity to some commercial fishers, it has also been prone to significant price fluctuations and the benefits accruing from it have not been widely shared. Accordingly, it has also been marked by frequent and often bitter conflicts between different crab fishing fleet sectors and between crab fishers, processing companies, and processing plant workers. These tensions reflect fundamentally different visions of how to sustain the fishery into the future and which priorities should decide who benefits most from the crab resource.